2020
DOI: 10.1097/j.pain.0000000000002052
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis coupled with extreme phenotype sampling identified that lysophosphatidylcholines are associated with multisite musculoskeletal pain

Abstract: Supplemental Digital Content is Available in the Text. Metabolic profiling coupled with extreme sampling identified lysophosphatidylcholines 26:0 and 28:1 to be potential biomarkers for multisite musculoskeletal pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 77 publications
1
28
0
Order By: Relevance
“…The ratio of LPC to PC has been reported to be associated with inflammation in severe OA and RA [ 43 , 44 ]. Consistent with one previous cross-sectional study [ 22 ], no association between the ratio of LPC to PC and MSMP was observed in the current study. Furthermore, our longitudinal analysis found no associations between ratio of LPC to PC and persistent MSMP.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The ratio of LPC to PC has been reported to be associated with inflammation in severe OA and RA [ 43 , 44 ]. Consistent with one previous cross-sectional study [ 22 ], no association between the ratio of LPC to PC and MSMP was observed in the current study. Furthermore, our longitudinal analysis found no associations between ratio of LPC to PC and persistent MSMP.…”
Section: Discussionsupporting
confidence: 93%
“…There are, to date, two studies from our group identifying MSMP-associated metabolites. We found that two bioactive proinflammatory lipid compounds, LPC (26:0 and 28:1), were positively associated with MSMP using the extreme phenotype sampling strategy [ 22 ]. More recently, we identified and replicated the association between an elevated SM C18:1 level and the presence of MSMP in two independent cohorts using different criteria of MSMP [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AAs could prove to be metabolites of several beneficial interventions, as they can modulate immune responses and, for instance, arginine is required for normal proliferation and maturation of T-cells, and it is involved in the macrophage class transition from M1 to M2, driving inflammation and resolution [ 66 ]. Bile acids [ 67 ] and pro-inflammatory LPCs [ 68 ] represent other metabolites that can be related to chronic pain and should be studied in more detail regarding joint diseases.…”
Section: Discussionmentioning
confidence: 99%
“… 12 In contrast, the current investigation is designed to minimize the conundrums apparent in previous studies of meditation and CVD by implementing an extreme phenotype sampling strategy, which has been used successfully in both genetic and metabolomic studies. 13 , 14 Specifically, we recruited 78 Tibetan Buddhist monks who engaged in meditation practice for a remarkable average of 19 years. The monks engaged in at least one hour per day of mediation with a mean time of 3.92 ± 3.21 h (range 1–15 h).…”
Section: Introductionmentioning
confidence: 99%